Long-term multi-wavelength studies of GRS 1915+105. I. A High-energy and mid-infrared focus with RXTE/INTEGRAL and SPitzer - Rahoui, F. (2010)
To date, mid-infrared properties of Galactic black hole binaries have barely been investigated in the framework of multi-wavelength campaigns. Yet, studies in this spectral domain are crucial to get complementary information on the presence of dust and/or on the physical processes such as dust heating and thermal bremsstrahlung. Here, we report a long-term multi-wavelength study of the microquasar GRS 1915+105. On the one hand, we aimed at understanding the origins of the mid-infrared emission, and on the other hand, at searching for correlation with the high-energy and/or radio activities. We observed the source at several epochs between 2004 and 2006 with the photometer IRAC and spectrometer IRS, both mounted on the Spitzer Space Telescope. When available, we completed our set of data with quasi-simultaneous RXTE/INTEGRAL high-energy and/or Ryle radio observations from public archives. We then studied the mid-infrared environment and activities of GRS 1915+105 through spectral analysis and broadband fitting of its radio to X-ray spectral energy distributions. We detected polycyclic aromatic hydrocarbon molecules in all but one IRS spectra of GRS 1915+105 which unambiguously proves the presence of a dust component, likely photoionized by the high-energy emission. We also argue that this dust is distributed in a disk-like structure heated by the companion star, as observed in some Herbig Ae/Be and isolated cool giant stars. Moreover, we show that some of the soft X-ray emission emanating from the inner regions of the accretion disk is reprocessed and thermalized in the outer part. This leads to a mid-infrared excess that is very likely correlated to the soft X-ray emission. We exclude thermal bremsstrahlung as contributing significantly in this spectral domain.